Pengaruh Motivasi Belajar, Mata Kuliah Praktik di Laboratorium, dan Magang Industri Terhadap Kesiapan dan Kemampuan Kerja Alumni Mahasiswa Akuntansi Politeknik Negeri Batam - Ely Kartikaningdyah; Arif Darmawan; Anjelina Angelina (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2013)
Batam Polytechnic is a public university that produces graduates with vocational competence and skill which is expected to be ready for the world of work. One of the courses has been producing graduates are courses in Accounting. In the learning process in the accounting curriculum of courses with subjects 40% theory and 40% practice course. Practice courses conducted at the Laboratory of Accounting in Accounting Studies curriculum Batam Polytechnic is expected to add to the understanding, skills and competencies of accounting and taxation courses. Over the many subjects of practice, is expected to produce graduates who have the skills and ready to work. Other subjects that support workready graduates that are subject Intern. In the implementation of learning, activity and discipline applied in the classroom or in the laboratory influence motivation, behavior and learning styles of students. The learning motivation can energize, encourage and determine behavior during the course to take and complete tasks in laboratory practices and Internships. The purpose of this research is to know how to influence the motivation to study, subjects in laboratory practices, and industrial internships either partially or together with the readiness and ability of the student alumni accounting Batam Polytechnic. Samples taken are alumni of accounting courses are already working. The analytical method used is the method of Causal-Comparative (Ex-Post Facto) is compared between before and after the incident after the fact-based case. The results of the research study motivation variable (X1) and practical laboratory courses (X2) indicates that the motivation to learn has no effect on the readiness of the ability to work (Y). Internship industry (X3) indicates that the apprenticeship industry has an influence on the readiness of the ability to work (Y)